Umedalen Skulptur 99. - Andersson, Stefan; Lundström, Jan Erik; Galleri Stefan Andersson, Umea (Umea : Umedalens skulpturpark, 1999)
Inc., Bonk Business ; Cragg, Tony (Anthony) ; Fischli & Weiss ; Fredriksson, Tina Eriksson ; Frederiksson, Christofer ; Hill, Gary ; Pétursson, Finnbogi ; Róbertsdóttir, Ragna ; Rollof, Ulf ; Tudvinen, Anu ; van Warmerdam, Marijke ; Balka, Miroslaw ; Bergström, Bigert & ; Englund, Lars ; Gianakos, Cristos ; Gormley, Antony ; Gunnars, Carina ; Hake, Claes ; Isaeus-Berlin, Meta ; Johansson, Peter ; Kapoor, Anish ; Kirschenbaum, Bernard ; Kjellgren, Ionas ; Naraha, Takashi ; Nonas, Richard ; Persson, Roland ; Rheinsberg, Raffael ; Schwartz, Buky ; Not Vital ; Wolgers, Dan ; Aberg, Mikael
biografie
Umedalen Skulptur 99, Umedalens skulpturpark, Umea, 5/6 - 5/9/1999
Engels & Zweeds
kunstcatalogus